Seeds tend to disperse further in the tropics - Si‐Chong Chen; Riin Tamme; Fiona J. Thomson; Angela T. Moles (Ecology Letters, 2019)
Despite the importance of seed dispersal in a plant's life cycle, global patterns in seed dispersal distance have seldom been studied. This paper presents the first geographically and taxonomically broad quantification of the latitudinal gradient in seed dispersal distance. Although there is substantial variation in the seed dispersal distances of different species at a given latitude, seeds disperse on average more than an order of magnitude further at the equator than towards the poles. This pattern is partially explained by plant life‐history traits that simultaneously associate with seed dispersal distance and latitude, including dispersal mode and plant height. The extended seed shadow of tropical plants could increase the distance between conspecific individuals. This could facilitate species coexistence and contribute to the maintenance of high plant diversity in tropical communities. The latitudinal gradient in dispersal distance also has implications for species’ persistence in the face of habitat fragmentation and climate change.